Repeated early-life exposure to anaesthesia and surgery causes subsequent anxiety-like behaviour and gut microbiota dysbiosis in juvenile rats. (February 2023) - Zhou, Xue; Xu, Xuanxian; Lu, Dihan; Chen, Keyu; Wu, Yan; Yang, Xiaoyu; Xiong, Wei; Chen, Xi; Lan, Liangtian; Li, Wenda; Shen, Shiqian; He, Wen; et al.
Abstract: Background: Early exposure to general anaesthetics for multiple surgeries or procedures might negatively affect brain development. Recent studies indicate the importance of microbiota in the development of stress-related behaviours. We determined whether repeated anaesthesia and surgery in early life cause gut microbiota dysbiosis and anxiety-like behaviours in rats. Methods: Sprague Dawley rats received skin incisions under sevoflurane 2.3 vol% three times during the first week of life. After 4 weeks, gut microbiota, anxiety-related behaviours, hippocampal serotonergic activity, and plasma stress hormones were tested. Subsequently, we explored the effect of faecal microbiota transplantation from multiple anaesthesia/surgery exposed rats after administration of a cocktail of antibiotics on anxiety-related behaviours. Results: Anxiety-like behaviours were observed in rats with repeated anaesthesia/surgery exposures: In the OF test, multiple anaesthesia/surgery exposures induced a decrease in the time spent in the centre compared to the Control group ( P <0.05, t =3.05, df=16, Cohen's d=1.44, effect size=0.58). In the EPM test, rats in Multiple AS group travelled less ( P <0.05, t =5.09, df=16, Cohen's d=2.40, effective size=0.77) and spent less time ( P <0.05, t =3.58, df=16, Cohen's d=1.69, effect size=0.65) in the open arms when compared to the Control group. Repeated exposure caused severe gut microbiota dysbiosis, with exaggerated stress response ( P <0.01, t =4.048, df=16, Cohen's d=−1.91, effect size=−0.69), a significant increase in the hippocampal concentration of 5-hydroxytryptamine (5-HT) and 5-hydroxyindoleacetic acid (5-HIAA) ( P <0.05; for 5-HT: t =3.33, df=18, Cohen's d=−1.49, effect size=−0.60; for 5-HIAA: t =3.12, df=18, Cohen's d=−1.40, effect size=−0.57), and changes in gene expression of serotonergic receptors later in life (for Htr1a: P <0.001, t =4.49, df=16, Cohen's d=2.24, effect size=0.75; for Htr2c: P <0.01, t =3.72, df=16, Cohen's d=1.86, effect size=0.68; for Htr6: P <0.001, t =7.76, df=16, Cohen's d=3.88, effect size=0.89). Faecal microbiota transplantation led to similar anxiety-like behaviours and changes in the levels of 5-hydroxytryptamine and 5-hydroxyindoleacetic acid. Conclusions: Gut microbiota dysbiosis caused by early repeated exposure to anaesthesia and surgery affects long-term anxiety emotion behaviours in rats.